STATUS HARA N P K DI SEKITAR PERAKARAN TANAMAN CABAI (Capsicum annum L) DI DESA WAWONA KECAMATAN TATAPAAN INDAH KABUPATEN SELATAN - Meisye G. Melale; Diane D. Pioh; Djoni Kaunang (Universitas Sam Ratulangi, 2017)
ABSTRACTPepper (Capsicum annuum L.), which include Family Solanaceae is a herbaceous plant taken the fruit that has a spicy flavor because it contains substances capsaisin. The study aims to determine the status of Hara N P K around rooting Plant Chilli (Capsicum annuum L) In the village of Wawona district of gaze Beautiful. This research was conducted in the village of Wawona for 2 months from February to March 2017. The research was conducted with survey method with direct observations in the field of further soil sampling for laboratory analysis. Nutrients observed that the content of nutrients around the plant roots chili. Results obtained the nitrogen in the soil around the roots mixed show is classified, elements phosphorus around the root range from medium to high and phosphorus in the soil around the roots mixed classified, elements potassium around the roots of a low to high and the soil around the roots are mixed, the content potassium is above the limit of potassium deficiency.Keyword: Status Hara, Nutrients N P K, Chili Plant